Combination of Aerial, Satellite, and UAV Photogrammetry for Quantifying Rock Glacier Kinematics in the Dry Andes of Chile (30°S) Since the 1950s - Vivero, Sebastián; Bodin, Xavier; Farías-Barahona, David; MacDonell, Shelley; Schaffer, Nicole; Robson, Benjamin Aubrey; Lambiel, Christophe (Frontiers in Remote Sensing, 2021)
The diachronic analysis of aerial and satellite imagery, uncrewed aerial vehicle (UAV) and in situ surveys obtained between 1956 and 2019 are employed to analyse landform surface kinematics for the Tapado site located in the Dry Andes of Chile. A feature tracking procedure was used between series of orthorectified and co-registered images to calculate surface velocities on several ice-debris landforms, including rock glaciers and debris-covered glaciers. For the active rock glaciers, the results exhibit typical viscous flow, though local destabilisation process seems to occur, increased velocities since 2000 (> 1 m/yr) and terminus advance. Nevertheless, the debris-covered glaciers displays heterogeneous spatial patterns of surface velocities, together with collapse (downwasting) associated with the development of thermokarst depressions and supraglacial ponds. Our findings show that surface kinematics and multitemporal observations derived from different sensors are valuable tools for differentiating between glacial and periglacial features. The pluri-decadal time series since 1956 constitute a unique dataset for documenting the surface kinematics of creeping mountain permafrost in the Southern Hemisphere. The approach developed in this work offers a way forward to reconstruct the recent behaviour of glacial and periglacial features in the Andes, where archival aerial photographs are available but have not previously been processed rigorously to obtain an accurate assessment of landform kinematics.